Strategic Management of Maternal and Child Health Services Improve Public Health Degree (Study on Implementation of SUTERA EMAS and EMAS Program in Malang Regency) - Laily Akbariah; Sarwono Sarwono; Endah Setyowati (Wacana Journal of Social and Humanity Studies, 2018)
Implementation of strategic management at the mother and children health services in Malang Regency is done through Sutera Emas and Emas Program. Both programs is grand strategy of Malang Regency to increase the societal health level measured from the AKI and AKB indicators. For that, the research aimed at describing and analyzing the implementation of Sutera Emas and Emas Program based on strategic management perspective, and identifying the obstacles occurred and producing alternative strategy for acceleration in decrease the AKI and AKB. So the used research method is qualitative by using descriptive analysis and foresight Approaches and Methods. The results showed that the implementation of Sutera Emas and Emas Programs are societal based program that use information technology to decrease AKI and AKB in Malang Regency. But the implementation of both program unable to be implemented wholly in Malang Regency. Because of that, it need alternative strategy for AKI and AKB decrease acceleration based on need assessment. The alternative strategy then be simulated based on three regions based on the criteria of standby village strata and the affordability of health service, either from the health service worker or health facilities.